OPTIMALISASI SISTEM INFORMASI MANAJEMEN UNTUK EFISIENSI OPERASIONAL: STUDI KASUS DIVISI ICT PT PERTAMINA ASSET 2 FIELD LIMAU - Frastio, Agiel; Ade Putra , Reza (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2025)
The optimization of Management Information Systems (MIS) is a key strategic step in enhancing operational efficiency at the ICT Division of PT Pertamina Asset 2 Field Limau. This process aims to address major challenges, such as inadequate system integration, manual data management, limited staff competence, and outdated technological infrastructure. Solutions implemented include system integration, automation technology adoption, staff training program development, and technology infrastructure upgrades. Results indicate that optimizing MIS reduces data redundancy, accelerates information processing, and supports more accurate data-driven decision-making. Innovative approaches like design thinking also contribute to system efficiency and user engagement improvement. In conclusion, optimizing MIS not only enhances operational efficiency but also strengthens the company's competitiveness in the energy sector through effective technology implementation and improved human resource management.